2016
DOI: 10.17159/2413-3086/2016/120
|View full text |Cite
|
Sign up to set email alerts
|

Religion: a new struggle for African identity

Abstract: Looking at most African countries, one realises that the social imaginaries which make us who we are, continue to be an issue in every society. It is even more rampant when we think of the role religion plays in determining who we are, what we believe and how we should act and react. This article seeks to look at the nature of religion and how religion over the years played a significant role in African identity. This article proposes that African identity has been endangered by religion; that there is a need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…African migrant families maintained their religious beliefs and faith; they found it easy to integrate into the host culture through religion (where their faith and beliefs are similar). Consistent with other research (Hirschman 2004;Sanni 2016), our study found that religion provides participants with a common ground to socialise, integrate and build a community with other co-migrants as well as native members of the host community. This was possible for all participants because religion supports the relevance of one's relationship with a higher power whereby the status quo is already set out.…”
Section: Discussionsupporting
confidence: 91%
“…African migrant families maintained their religious beliefs and faith; they found it easy to integrate into the host culture through religion (where their faith and beliefs are similar). Consistent with other research (Hirschman 2004;Sanni 2016), our study found that religion provides participants with a common ground to socialise, integrate and build a community with other co-migrants as well as native members of the host community. This was possible for all participants because religion supports the relevance of one's relationship with a higher power whereby the status quo is already set out.…”
Section: Discussionsupporting
confidence: 91%
“…Os achados que consideraram a intolerância religiosa como conflito político, religioso e identitário evidenciaram a necessidade de aprimoramento das leis protetivas e fortalecimento da consciência de grupos étnicos minoritários em torno da compreensão conceitual sobre religião e identidade africana (Osborn, 2014, Sanni, 2016. E os achados que consideraram a intolerância religiosa como violação aos direitos humanos, com afetação a liberdade religiosa, demonstraram que litígios religiosos suscitam debates sobre questões de identidade, diferença, preconceito e religião, que são levadas aos Tribunais em busca de posicionamentos e mudanças legislativas e jurídicas, pois interferem na construção sócio política e cultural das sociedades (Du Plessis, 2009, Gualberto, 2011, Benson, 2013, Santos, 2016, Fonseca e Adad, 2016, Brasil, 2017, Embaixada dos Estatos Unidos No Brasil, 2019, Nation, 2019.…”
Section: Resultsunclassified
“…In other words, to exist as a person in a community is to abide by the precepts, morals, and values of that community. Referring to belonging, Sanni, in his paper “Decolonising Borders: Re‐imagining Strangeness and Spaces,” argues that what binds people in most African societies are the geographical, social, and historical narratives that inform the collective understanding of knowledge, and these may valorise and reinforce a negative conception of strangeness and exclusion of others (2020, p. 4; See Sanni, 2016). However, this sense of society may also promote a strong sense of community of persons with shared values.…”
Section: The Possibility Of Radical Escape In Ubuntumentioning
confidence: 99%